Novel oncogene and tumor suppressor mutations in KIT and PDGFRA wild type gastrointestinal stromal tumors revealed by next generation sequencing. Issue 3 (27th November 2014) - Hechtman, Jaclyn Frances; Zehir, Ahmet; Mitchell, Talia; Borsu, Laetitia; Singer, Samuel; Tap, William; Oultache, Alifya; Ladanyi, Marc; Nafa, Khedoudja
<x xml:space="preserve">Abstract</x> Among gastrointestinal stromal tumors (GISTs) of 10–15% are negative for KIT and PDGFRA, and most of these cases are SDH deficient. Recent studies have provided data on additional molecular alterations such as KRAS in KIT mutant GISTs. We aimed to assess the frequency and spectrum of somatic mutations in common oncogenes as well as copy number variations in GISTs negative for KIT and PDGFRA mutations. GISTs with wild type KIT/PDGFRA were tested via next generation sequencing for somatic mutations in 341 genes. SDHB immunohistochemistry to evaluate for SDH deficiency was also performed. Of 267 GISTs tested for KIT and PDGFRA mutations, 15 were wild type, of which eight cases had material available for further testing. All eight cases had loss of SDHB expression and had various molecular alterations involving ARID1A, TP53, and other genes. One case had a KRAS G12V (c.35G>T) mutation in both the primary gastric tumor and a post‐imatinib recurrence. This tumor had anaplastic features and was resistant to multiple tyrosine kinase inhibitors, ultimately resulting in cancer‐related mortality within 2 years of diagnosis. In conclusion, KRAS mutations occur in rare GISTs with wild type KIT and PDGFRA. These tumors may display immunohistochemical positivity for KIT and primary resistance to tyrosine kinase inhibitors. © 2014 Wiley Periodicals, Inc.